2019
DOI: 10.1021/jacs.9b09234
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Energy Level of Metal Center: Ru Single-Atom Site for Efficient and Durable Oxygen Reduction Catalysis

Abstract: Emerging as a new frontier in heterogeneous catalysis, single-atom site catalysts (SSCs) have sparked enormous attention and bring about new opportunities to oxygen reduction electrocatalysis. Despite considerable progress achieved recently, most of the reported SSCs suffer from either insufficient activity or unsatisfactory stability, which severely retards their practical application. Here, we demonstrate a novel Ru-SSC with appropriate adsorption free energy of OH* (ΔG OH*) to confer excellent activity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
198
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(208 citation statements)
references
References 38 publications
8
198
0
2
Order By: Relevance
“…22 All the above characterizations confirm the preservation of carbon nitride's structure after loading Ru species, while the specific peaks assigned to Ru species are not observed, again due to the highly dispersed and low amount of Ru loaded. 23,24 TEM was applied to analyse the microstructures of photocatalysts after loading Ru and RuO 2 (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…22 All the above characterizations confirm the preservation of carbon nitride's structure after loading Ru species, while the specific peaks assigned to Ru species are not observed, again due to the highly dispersed and low amount of Ru loaded. 23,24 TEM was applied to analyse the microstructures of photocatalysts after loading Ru and RuO 2 (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The above results suggested that the presence of abundant atomically dispersed Ru-O 2 sites is responsible for the significant performance enhancement, as will be discussed later. Moreover, compared to the reported Ru SA catalysts (including single-, dual-, or trifunctional catalysts), [15,16,19,20,27,29,50] our designed Ru single-site catalyst exhibits a competitive advantage in acidic media (Details have been provided in Tables S2-S7, Supporting Information), highlighting the importance of engineering the coordination environment of a single site on its catalytic activity.…”
Section: Orr Performance In Acidic Mediamentioning
confidence: 98%
“…Theoretical calculations revealed that ORR activity of Ru-N/G-750 originated from the Ru-oxo-N 4 moieties rather than Ru-N 4 moieties [ 148 ]. Xiao et al further reported that a Ru-based SAEC (Ru-SSC) showed unprecedented TOF up to 4.99 e − s −1 site −1 , far surpassing the benchmark Fe-SSC counterpart (0.816 e − s −1 site −1 ) [ 149 ].The excellent ORR activity of Ru-SSC could be attributed to the suitable OH∗ adsorption-free energy. In addition, Ru-SSC showed low Fenton reactivity, which enables the Ru-SSC much better durability (only 17 mV negative shift after 20000 cycles) than the corresponding Fe-SSC catalyst (31 mV).…”
Section: Saecs For Oxygen Reduction Reactionsmentioning
confidence: 99%